(untitled) (Моделювання, керування та інформаційні технології, 2021)
An automatic control system for remote control and monitoring of bee life parameters in hives is developed. Based on the research of the main parameters of the life of bees in the hive, we have developed a scheme for managing and monitoring the weight of the hive, temperature and humidity, noise level, prevention of theft.